The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5380/avs.v13i1.11560
|View full text |Cite
|
Sign up to set email alerts
|

METODOLOGIA PARA QUANTIFICAÇÃO DE LEUCÓCITOS TOTAIS EM PEIXE, <i>OREOCHROMIS NILOTICUS</i>

Abstract: resumo -O estudo da hematologia é considerado uma importante ferramenta para o processo de diagnóstico de doenças. As técnicas usadas em mamíferos são amplamente aplicadas em peixes, no entanto com algumas modificações. A presença de eritrócitos nucleados e trombócitos em peixes pode causar dificuldade na identificação das cé-lulas sangüíneas, principalmente na contagem de leucócitos totais. A presente pesquisa foi realizada com o objetivo de avaliar duas metodologias (direta e indireta) de quantificação de le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 3 publications
1
18
1
2
Order By: Relevance
“…Hrubec et al (2000) also does not report the occurrence of Bf and SGC in Oreochromis niloticus. On the other hand, the values obtained in this study were superior to those found by Ishikawa et al (2008), where a direct methodology to count WBC for O. niloticus maintained in ponds was used. The mean value of WBC for O. niloticus, in the present study, was lower than the findings of Falcon et al (2008) The leukocytes are useful for assessing the immune system and variations in the proportion of these cells are considered normal (Tavares-Dias & Moraes, 2006).…”
contrasting
confidence: 40%
“…Hrubec et al (2000) also does not report the occurrence of Bf and SGC in Oreochromis niloticus. On the other hand, the values obtained in this study were superior to those found by Ishikawa et al (2008), where a direct methodology to count WBC for O. niloticus maintained in ponds was used. The mean value of WBC for O. niloticus, in the present study, was lower than the findings of Falcon et al (2008) The leukocytes are useful for assessing the immune system and variations in the proportion of these cells are considered normal (Tavares-Dias & Moraes, 2006).…”
contrasting
confidence: 40%
“…One aliquot was used to determine hematocrit (Goldenfarb et al 1971) and the rest was stored in glass flasks on ice to quantify the total number of erythrocytes in a hemocytometer. Total number of thrombocytes and leukocytes were counted in blood extension by the indirect method described by Ishikawa et al (2008). One aliquot of serum was used to determine glycemic index in spectrophotometer (Biotécnica ® kit) at 505 nm.…”
Section: Hematology and Glucosementioning
confidence: 99%
“…Total leukocytes count (WBC) and differential leukocytes count were determined in blood smears stained by May-Grünwald-Giemsa (Rosenfeld, 1947). WBC number was calculated using the formula: leukocytes/μl = (leukocyte number in the smear x erythrocyte number/ μl)/2,000 erythrocytes counted in the smear, as described by Ishikawa et al (2008).…”
Section: Methodsmentioning
confidence: 99%